Pemanfaatan Sound book sebagai Media Pembelajaran Interaktif Al-Qur’an Hadis - Khoiru Nurfitri; Indah Puji Astuti; Jawwad Sulthon Habiby (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
One way to use technology in creating learning media is by combining audio and visual elements. A heterogeneous society is facing various challenges in the field of education, especially in learning. Islamic Religious Education at the Elementary School (SD) Teacher Working Group (KKG) Islamic Religious Education (PAI) level in Balong sub-district has become a relevant partners to overcome these challenges. The situation analysis shows that the PAI KKG Balong District is still facing several problems that need to be resolved. Among them is the lack of use of interactive learning media, especially for PAI subjects in grade 1 elementary school. This results in a lack of student enthusiasm in learning, considering the importance of interactive and innovative learning media in motivating students at the elementary school education level. This is one of them Alternative examples of optimization efforts in the teaching and learning process. The hope is that students will have high enthusiasm and motivation to learn. This study uses interview techniques to identify and map the problems faced by partners, followed by analysis of the interview results, and then creating a sound book design. The result of this activity is the design of a sound book as an interactive learning media for Al-Qur'an Hadith. It is hoped that the results of the sound book design, after testing by partners, can be continued to the production stage as a media to attract student enthusiasm in the teaching and learning process.